Gastrointestinal stromal tumor of the pancreas: a case report and review of the literature - Bertozzi, Serena; Londero, Ambrogio P.; Cherchi, Vittorio; Basso, Stefania; Canzonieri, Vincenzo; Bacchetti, Stefano; Uzzau, Alessandro (European Journal of Oncology and Environmental Health, 2014)
Gastrointestinal stromal tumours (GIST) represent a rare borderline neoplastic disease, which is currently thought to arise from the interstitial cells of Cajal, very few cases of pancreatic GIST having been reported so far. We report a case of a 60 year-old man with an incidental imaging (MRI) finding of a solid mass in the pancreatic head, which histological examination revealed to be a GIST. The patient had a disease recurrence after 42 months, received systemic treatment with Imatinib with benefit, and is still alive 53 months after diagnosis with a good quality of life. Although the studies published on pancreatic GIST are rare, we agree with most authors that GIST should always be considered in the differential diagnosis of a solid pancreatic mass, and a preoperative histological diagnosis possibly supported by intraoperative histological confirmation may be remarkably useful in order to tailor the surgical approach. Finally, despite its high risk, pancreatic GIST does not imply a poor prognosis if correctly treated by loco-regional surgical excision: its course depends on handling any complications of major abdominal surgery, which may be very serious in the case of the pancreatic localization.